Analisis Kesiapsiagaan Masyarakat dalam Menghadapi Bencana Banjir di Multatuli, Medan Maimun - Nuraini Fadilah; Susilawati Susilawati; Shinta Aulia Agusta; Natasya Balqis; Dwi Ulan Dari (Pusat riset dan Inovasi Nasional, 2026)
Multatuli Area 4 is highly susceptible to flooding due to its close location to the Deli River and inadequate environmental management, which exacerbate the risk during the rainy season. Despite this vulnerability, community preparedness remains limited, leaving residents exposed to potential damage and loss. This study employed a descriptive qualitative approach, collecting data through in-depth interviews and direct observations with purposively selected informants who have knowledge of local flooding experiences. The findings reveal that while residents are generally able to recognize early signs of flooding, their responses are largely reactive rather than proactive. Several factors contribute to this low level of preparedness, including limited perception of risk, insufficient economic capacity to implement preventive measures, declining social cohesion and cooperation, and underutilization of available mitigation facilities and infrastructure. These conditions highlight the need for improved community awareness, better access to resources, and strengthened disaster management strategies to enhance flood preparedness in Multatuli Area 4.